Hubungan pengembangan karir perawat terhadap kualitas pelayanan keperawatan di rumah sakit: Relationship of nurse career development to quality of nursing services in hospital - hardiansah, yayan (Stikes Wira Medika Bali, 2021)
Background: nursing career development is a planning and implementation of a career plan Change has become the norm and creates an environment in which individuals must be able to control their careers. With the implementation of career development, you will be able to control your career and achieve a better career and good nursing services. The purpose of this study was to determine the career development of nurses based on hospital policies on the quality of nursing services at Tugurejo General Hospital Semarang and Sultan Agung Hospital Semarang. Methods: The type of research is descriptive analytic using cross sectional. The population of all implementing nurses on duty in inpatient installations with a population of 453 at Tugurejo General Hospital Semarang and 262 nurse managers at Sultan Agung Hospital Semarang 2017. Determination of the sample using stratified random sampling. analyzed include univariate , bivariate , multivariate with logistic regression test . Data using a questionnaire. Results: There is a significant relationship between the career development of nurses with the implementation of rotational mutations on the quality of nursing services at Tugurejo Hospital, Semarang with p = 0.039 and exo (b) 0.369